Dialectical tension between Police Violence and Child Violence: Perspective of Human Rights and Child Protection Law - Kadir, Arianto; Melki Kumaat; Glen Oroh; Grace M.A. Dengah; Syafaruddin (Jurnal Saintifik (Multi Science Journal), 2023)
Violent acts committed by police officers in the process of arresting children in conflict with the law are a serious problem in law enforcement that is just, certain and beneficial. This study aims to analyze this practice from the perspective of Human Rights (HAM) and the Child Protection Law in Indonesia. This study uses a normative legal approach with a literature study technique on relevant laws and regulations, legal literature, and international conventions. The results of the analysis show that violent acts by officers against children violate the principles of non-violence, restorative justice, and children's rights to protection as regulated in Law No. 11 of 2012 concerning the Juvenile Criminal Justice System and Law No. 35 of 2014 concerning Child Protection. Highlights the importance of policy reform and officer training to ensure that the handling of children in legal conflict is carried out in a humane, proportional, and child-rights-based manner. The implications of this study emphasize that law enforcement that is not child-friendly has the potential to damage children's future and harm the principles of the rule of law